Economic Valuation of Tojang Spring, East Lombok - Mubarok, Lalu Rifki; Afifi, Mansur; Diswandi, Diswandi (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
Water resource existence in the rural area faces many challenges and threats driven by climate changes or socio-economic activity. As one of few water resources in East Lombok, Tojang spring face degradation threats due to the rapid growth of population and its activity. This study adopted a stated preference approach to investigate willingness to pay for the conservation and maintenance of Tojang spring and its influencing factors. Data was collected through a survey of 100 households which were selected randomly. As part of the findings, the survey result showed evidence that the majority of the respondent was willing to pay an average of IDR 8,350 per month with an annual economic value of IDR 1,144,584,600.00. Influencing factors that determined willingness to pay include age, household income, education, family size, water bill, length of usage, water quantity, and existence value. This study seeks to provide information that could affect decision-making toward the restoration and development of Tojang spring for its sustainability.